Preliminary Characterization, Antioxidant and Antiproliferative Properties of Polysaccharide from Caulerpa taxifolia - Bayro, Ariane Marie; Manlusoc, Joanne Katherine; Alonte, Renaliza; Caniel, Catherine; Conde, Patrick; Embralino, Carlo (Pharmaceutical Sciences and Research, 2021)
Macroalgae are abundant sources of bioactive polysaccharides and prospective candidates for effective and non-toxic substances. This study aims to preliminary characterize and determine the in vitro antioxidant activity and cancer cell growth inhibitory activity against human lung adenocarcinoma cell (A549) of the polysaccharide from an invasive green alga, Caulerpa taxifolia. Crude polysaccharide (CP) was extracted from the dried algal sample of C. taxifolia by hot water extraction followed by absolute ethanol precipitation. CP was subjected to preliminary chemical characterization, including protein, carbohydrate, and sulfate content analysis by Kjeldahl titrimetry, acid hydrolysis, gravimetry, and ashing-acid water digestion ion chromatography, respectively. Functional groups present in the CP were determined by Fourier transform infrared spectroscopy (FT-IR). Antioxidant activity was evaluated by 1, 1-diphenyl-2-picrylhydrazyl radical (DPPH) free radical scavenging activity assay. The cancer cell growth inhibitory activity against A549 cells was evaluated by MTT assay. Chemical composition of the CP shows 68.4 % (w/w) carbohydrate, 9.4% (w/w) protein, and 0.74% (w/w) sulfate. FT-IR showed the presence of -OH group, C-H stretch groups, C=O groups, and C-O groups and suggested a pyranose configuration of the sugar structure. MTT assay showed the highest inhibition at 25 μg/mL concentration with 35.50% ± 1.66 SEM with a relative IC50 of 45.44 μg/mL. However, the DPPH assay did not exhibit remarkable free radical scavenging capacity than other studies of polysaccharides with only 18.33% at 1 mg/mL. This exploratory study paves the way to explore the mechanism of action of polysaccharides from marine algae as a possible anticancer treatment.